COMPLICATIONS IN RHEUMATOID ARTHRITIS PATIENTS FOLLOWING KNEE JOINT REPLACEMENT: FINDINGS FROM A 26-WEEK PROSPECTIVE REAL-WORLD COHORT STUDY (Journal of Universal Science Research, 2025)
Anorboev, M., Akhmedov, K., & Khujanazarov, I. (2025). COMPLICATIONS IN RHEUMATOID ARTHRITIS PATIENTS FOLLOWING KNEE JOINT REPLACEMENT: FINDINGS FROM A 26-WEEK PROSPECTIVE REAL-WORLD COHORT STUDY. "FARMAKOLOGIYA, FARMATSEVTIKA VA XALQ TABOBATI: DOLZARB MUAMMOLAR VA INNOVATSIYALAR" MAVZUSIDAGI XALQARO ILMIY-AMALIY KONFERENSIYASI, 1(1), 85–85. https://doi.org/10.5281/zenodo.17855563